Lissothuria imbricata sp. nov., a new species of sea cucumber (Echinodermata: Holothuroidea) from the central-eastern Pacific Ocean - Solís-Marín, Francisco Alonso; Arriaga-Ochoa, Julio Adrian; Villa, Cristian Moises Galvan; Laguarda-Figueras, Alfredo (Zootaxa, 2018)
A new species of sea cucumbers of the genus Lissothuria Verrill, 1867 is described. Lissothuria imbricata sp. nov. was found in the central-eastern Pacific Ocean, at 2–16 m depth living on top of rocky reefs, partially covered by algae and organic material. It is distinguished from other species of the genus by having body wall ossicles in form of short, broad towers with a slightly spiny apex, giving the dorsal area a granular appearance. The shape of the ossicles shows some similarities with L. nutriens (H.L. Clark, 1901).